2008
DOI: 10.1016/j.addr.2008.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Driving delivery vehicles with ultrasound

Abstract: Therapeutic applications of ultrasound have been considered for over 40 years, with the mild hyperthermia and associated increases in perfusion produced by ultrasound harnessed in many of the earliest treatments. More recently, new mechanisms for ultrasound-based or ultrasound-enhanced therapies have been described, and there is now great momentum and enthusiasm for the clinical translation of these techniques. This dedicated issue of Advanced Drug Delivery Reviews, entitled "Ultrasound for Drug and Gene Deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
167
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(168 citation statements)
references
References 61 publications
1
167
0
Order By: Relevance
“…In brief, local US insonation of a pathologic condition (e.g. tumor) containing microbubbles in vascular compartments induces bubble oscillations (stable or inertial cavitation) which lead to a variety of biomechanical effects that enhance extravasation and distribution of drug molecules to target tissue [9][10][11][12][13][14]. This approach may hence be explored to improve on the local specificity of a drug, either co-injected with, or attached to microbubbles.…”
Section: Introductionmentioning
confidence: 99%
“…In brief, local US insonation of a pathologic condition (e.g. tumor) containing microbubbles in vascular compartments induces bubble oscillations (stable or inertial cavitation) which lead to a variety of biomechanical effects that enhance extravasation and distribution of drug molecules to target tissue [9][10][11][12][13][14]. This approach may hence be explored to improve on the local specificity of a drug, either co-injected with, or attached to microbubbles.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that gas-containing particles are highly sonosensitive (Huang et al, 2008;Unger et al, 1998;Huang and MacDonald., 2004). Unfortunately, gas-filled liposomes are micron-sized and thus too large to allow for effective extravasation into tumour tissue (Ferrara, 2008;Maeda et al, 2000). Another limitation of such particles is the rapid dissolution of the entrapped gas in blood circulation with consequent loss of sonosensitivity (Unger et al, 1998;Ferrara, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound has many clinical advantages as a gene delivery system, due its easy and reliable procedure (Pitt et al, 2004;Ferrara, 2010). In recent years, it was found that microbubbles applied by ultrasound increased gene expression.…”
Section: Ultrasoundmentioning
confidence: 99%